PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP SIKAP ETIS MAHASISWA AKUNTANSI (Studi Empiris pada Mahasiswa Prodi Akuntansi di Universitas Islam Malang dan Universitas Islam Negeri Maulana Malik Ibrahim) - Nanik Risma Nadia; Moh. Amin; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study is to the influence of intellectual intelligence, emotional intelligence and spiritual intelligence on the ethical attitudes of accounting students at the Islamic University of Malang and the State Islamic University Of Maulana Malik Ibrahim, either partially or simultaneously. This research is causal comparative with quantitative approach. The data processed in this study is primary data as many as 196 respondents with Purposive Sampling technique. The technique of collecting data is through distributing questionnaires through google form. From the results of multiple linear regression tests using SPSS 16 software, it can be seen that there is a positive and significant influence on intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) on the ethical attitudes of accounting students. It is partially proven that each of the three independent variables has a significant value from the t test <0.05. and proved again simultaneously to obtain a significant value of F < 0.05. Keywords : Student Ethical Attitude, Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence